Chronological Reorganization of Microtubules, Actin Microfilaments, and Chromatin during the First Cell Cycle in Swamp Buffalo (Bubalus bubalis) Embryos - Vibuntita Chankitisakul; Theerawat Tharasanit; Kriengsak Tasripoo; Mongkol Techakumphu (Veterinary Medicine International)
This paper aimed to study the dynamics of early embryonic development, in terms of redistribution of cytoskeleton (microtubules, actin microfilaments) and chromatin configurations during the first cell cycle in swamp buffalo embryos. Oocytes were matured and fertilized in vitro, and they were fixed at various time points after IVF. At 6 h after IVF, 44.4% matured oocytes were penetrated by spermatozoa. Partial ZP digestion, however, did not improve fertilization rate compared to control (P>.05). At 12 h after IVF, the fertilized oocytes progressed to the second meiotic division and formed the female pronucleus simultaneously with the paternal chromatin continued to decondense. A sperm aster was observed radiating from the base of the decondensing sperm head. At 18 h after IVF, most presumptive zygotes had reached the pronuclear stage. The sperm aster was concurrently enlarged to assist the migration and apposition of pronuclei. Cell cleavage was facilitated by microfilaments and firstly observed by 30 h after IVF. In conclusion, the cytoskeleton actively involves with the process of fertilization and cleavage in swamp buffalo oocytes. The centrosomal material is paternally inherited. Fertilization failure is predominantly caused by poor sperm penetration. However, partial digestion of ZP did not improve fertilization rate.